2021
DOI: 10.1002/jemt.23809
|View full text |Cite
|
Sign up to set email alerts
|

Acmella oleracea extract increases collagen content and organization in partially transected tendons

Abstract: Acmella oleracea contains spilanthol as the main active compound, which possesses analgesic and anti‐inflammatory effects that can favor tendon reorganization. To analyze the effect of A. oleracea on the content and organization of collagen in injured tendons, the calcaneal tendon of male Lewis rats was partially transected and treated at the site of injury with a topical application of 20% A. oleracea ointment (AO group) or with the ointment base without the plant extract (B group). The animals were euthanize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“… 9 Theoretically, it may support the native skin microbiome, which has the potential to affect age-related changes in this complex system. Acmella oleracea extract has been shown in preclinical models to improve collagen content and organization following tendon injury 10 and also has both anti-inflammatory and antioxidant activities. 11 Astaxanthin ( H. pluvialis extract) is a potent antioxidant with a unique capacity to quench reactive oxygen species in the cell membrane through inhibition of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Theoretically, it may support the native skin microbiome, which has the potential to affect age-related changes in this complex system. Acmella oleracea extract has been shown in preclinical models to improve collagen content and organization following tendon injury 10 and also has both anti-inflammatory and antioxidant activities. 11 Astaxanthin ( H. pluvialis extract) is a potent antioxidant with a unique capacity to quench reactive oxygen species in the cell membrane through inhibition of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Acmella oleracea may also favor tendon repair, via increasing the molecular organization and content of collagen in partially transected tendons. 138 Whether this effect help restore the impaired ECM in aged skin needs further studies.…”
Section: Promising Naturally Derived Ingredients From An Anti-ageing ...mentioning
confidence: 99%
“…Yamane et al showed that jambù helped in collagen deposition and decreased the time of the healing process [ 61 ]. Moreover, de Souza Moro et al demonstrated that A. oleracea increased the molecular organization and content of collagen [ 103 ].…”
Section: Biological Activitiesmentioning
confidence: 99%